Psychological Distress and Finding Meaning in the COVID-19 Pandemic: Social Connectedness and Media Use - Özdemir, Fatih; Çeviker, Gizem (Lut TAMAM, 2021)
The purpose of this study is to focus on people’s psychological distress, the degree as to how meaningful they consider their lives during a period in which the COVID-19 pandemic has affected Turkey substantially, as well as to examine the relationship between these concepts and certain demographic variables, social ties with local or extended groups, and the use of social and traditional media. The study includes 1023 participants (828 of which are female and 195 are male) between the ages of 18-46. In parallel with the study hypotheses, women (compared to men) scored higher in the variables of finding meaning in life, local social ties, extended social ties and the use of traditional media. Those who have a perception of strong social ties with their local group (family members, friends, co-workers, and neighbors) and extended group (the city and the country they live in) during the pandemic consider life more meaningful. However, the psychological distress claimed by those who have a perception of stronger ties with their local group is stronger. While the perceived psychological distress of those who follow the developments regarding the pandemic on social and/or traditional media more closely are stronger, those who follow traditional media have a higher degree of considering their life more meaningful. Determining the level of psychological distress perceived by the people and how meaningful they consider life during the early stages of the pandemic, and to ascertain the related variables fills a major gap in the pandemic-based literature that is still growing and provides a source of information for the interventional studies to be conducted.

Çalışmanın amacı COVID-19 pandemisinin Türkiye'yi yoğun olarak etkilediği dönemde kişilerin psikolojik huzursuzluk ve hayatı anlamlı bulma düzeylerine odaklanmak ve bu kavramların belirli demografik değişkenler, yerel/geniş gruplara yönelik sosyal bağlar ve sosyal/klasik medya kullanımıyla olan ilişkilerini incelemektedir. Çalışmaya 18-46 yaş aralığında bulunan 1023 kişi (828 kadın, 195 erkek) katılmıştır. Araştırma hipotezleriyle tutarlı olarak, erkeklere kıyasla kadınlar hayatı anlamlı bulma, yerel sosyal bağ, geniş sosyal bağ ve klasik medya kullanımı değişkenlerinde daha yüksek skorlara sahiptir. Pandemi sürecinde yerel gruba (aile bireyleri, arkadaşlar, işyerindeki/okuldaki kişiler ve komşular) ve geniş gruba (yaşanılan şehir ve ülke) yönelik kuvvetli sosyal bağlar algılayan kişiler hayatı daha anlamlı bulmaktadır. Fakat yerel gruba yönelik kuvvetli sosyal bağlar algılayan kişilerin belirttikleri psikolojik huzursuzluk daha kuvvetlidir. Pandemiye ilişkin gelişmeleri sosyal ve/veya klasik medya mecralarından daha fazla takip eden kişilerin algıladıkları psikolojik huzursuzluk daha kuvvetliyken, klasik medya mecralarını takip eden kişilerin hayatı anlamlı bulma düzeyleri daha yüksektir. Pandeminin başladığı dönemde kişilerin ne ölçüde psikolojik huzursuzluk algıladığını ve hayatlarını anlamlı bulduğunu saptamak ve ilişkili değişkenleri belirlemek pandemi-temelli gelişmekte olan alanyazında önemli bir boşluğu doldurmakta ve uygulanacak müdahale çalışmaları için bilgi sağlamaktadır.
COVID-19 Pandemisinde Algılanan Psikolojik Huzursuzluk ve Anlam Bulma: Sosyal Bağlar ve Medya Kullanımı
Keywords: Psychology; Psikoloji